The Effect of Pulsed Electromagnetic Field on the Bone Volume of Human Being. (2015) - Wang, Yanan; Zhang, Wei
Abstract: Pulsed electromagnetic fields (PEMF) devices have been used clinically to slow down osteoporosis and accelerate the healing of bone fractures for many years. However the underlying mechanism by which bone remodeling under PEMF is regulated remains poorly understood. In this paper, a mathematical model of bone cell population of bone remodeling under PEMF at cellular level is developed to address this issue for the first time. Based on this model and control theory, parametric study of control mechanism is carried out and a number of possible control mechanisms are identified. These findings would help further understanding of bone remodeling under PEMF and potential therapies and pharmacological developments in clinical trials.